Possible error in the Danish version of the WHO Quality of Life (WHOQOL-BREF) Questionnaire. (3rd October 2017) - Thomsen, Ane Søndergaard; Bech, Per
Abstract: Background: The WHOQOL-BREF is widely used to measure quality of life. Aims: The goal of the present study was to use the questionnaire in a doctoral study. Methods: We studied all the instructions provided by the WHO. Results: In the Danish version of the WHOQOL-BREF there is a discrepancy between the negatively phrased question 9 and both the syntax file and the verbal instructions for coding the data provided by the WHO. Conclusions: This is a notification of possible error interpretations in projects that use the questionnaire. This could be corrected by manual correction in the coding process or by changing the negatively phrased question 9.